Organizational Members’ Communication and Temporal Experience : Scale Development and Validation - Ballard, Dawna I. and Seibold, David R. (Communication Research, 2004)
This article reports the findings of scale development and validation efforts centered on 10 dimensions of organizational members’ temporal experience identified in previous research. Consistent with a community-of-practice perspective, 395 members of five organizational units indicated their agreement with a series of statements regarding the day-to-day words and phrases they use to describe their activities, work-related events, and general timing needs. Results of a confirmatory factor analysis provided support for the hypothesized enactments of time and construals of time. Organizational members’ enactments of time included dimensions relating to flexibility, linearity, pace, precision, scheduling, and separation, and their construals of time included dimensions concerning scarcity, urgency, present time perspective, and future time perspective. A new dimension, delay, was found. Implications for pluritemporalism in organizations and the study of time in communication are discussed.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjAzMjYxNTA0